2002
DOI: 10.1021/ma020285v
|View full text |Cite
|
Sign up to set email alerts
|

Novel Poly(p-phenylenevinylene)s with an Electron-Withdrawing Cyanophenyl Group

Abstract: Novel poly(p-phenylenevinylene) derivatives with an electron-withdrawing cyanophenyl group on the polymer backbone, poly[2-(2‘-ethylhexyloxy)-5-(4‘-cyanophenyl)-1,4-phenylenevinylene] (PEHCNPV) and poly[2-dimethyloctylsilyl-5-(4‘-cyanophenyl)-1,4-phenylenevinylene] (PSi8CNPV), were synthesized via the Gilch polymerization. These polymers were completely soluble in common organic solvents and showed good thermal stability up to 400 °C. Surprisingly, they showed very high glass transition temperatures (above 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…39), were synthesized via the Gilch polymerization [175]. They showed very high glass transition temperatures (above 180 • C).…”
Section: Tuning the Color Of Silyl-disubstituted Ppvs Is Possible By mentioning
confidence: 99%
“…39), were synthesized via the Gilch polymerization [175]. They showed very high glass transition temperatures (above 180 • C).…”
Section: Tuning the Color Of Silyl-disubstituted Ppvs Is Possible By mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Recently, although there are some reports concerning the improvement of the chromaticity coordinate, the results are not satisfactory, due to either a complicated procedure for the synthesis of the polymers or impure emitting. [15][16][17][18][19][20][21] It is noted that the current color standard established by the Society of Motion Picture and Television Engineers (SMPTE) in 1979 (SMPTE-C, e.g., NTSC 1979) has been widely used in fields related to flat panel display. [22] Thus, investigation of the synthesis and properties of the materials that match with the standard is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…n It has been found that most polymeric green emitters are derived from the fluorene-based polymers, and those polymers are usually constituted of a rich-electron fluorene unit and a deficient-electron unit. [13,[15][16][17][18][19][20] The green emission is attributed to intramolecular charge transfer. Of these polymers, the electron-withdrawing degree of the deficient-electron unit greatly affects the emission wavelength of the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Balancing the rates of injection of electrons and holes from opposite electrodes into the light-emitting polymer is required to achieve the high electroluminescence efficiency. Using additional organic charge-transporting layers, 19,20 and adjusting the energy band of the polymer by introduction of electron-withdrawing groups attached to the polymer backbone 21,22 were reported to overcome the imbalance of charge carrier injection or mobility. It was reported that the HOMO and LUMO energy levels can be lowered by the introduction of electron-withdrawing groups onto the arylene rings or the vinylene groups of the polymer.…”
Section: Introductionmentioning
confidence: 99%